Honing the Double-Edged Sword: Improving Human iPSC-Microglia Models - Hedegaard, Anne; Stodolak, Szymon; James, William S.; Cowley, Sally A. (Frontiers in Immunology, 2020)
Human induced Pluripotent Stem Cell (hiPSC) models are a valuable new tool for research into neurodegenerative diseases. Neuroinflammation is now recognised as a key process in neurodegenerative disease and ageing, and microglia are central players in this. A plethora of hiPSC-derived microglial models have been published recently to explore neuroinflammation, ranging from monoculture through to xenotransplantation. However, combining physiological relevance, reproducibility, and scalability into one model is still a challenge. We examine key features of the in vitro microglial environment, especially media composition, extracellular matrix, and co-culture, to identify areas for improvement in current hiPSC-microglia models.